Efficient recombinant production of prodigiosin in Pseudomonas putida - Domröse, Andreas; Klein, Andreas S.; Hage-Hülsmann, Jennifer; Thies, Stephan; Svensson, Vera; Classen, Thomas; Pietruszka, Jörg; Jaeger, Karl-Erich; Drepper, Thomas; Loeschcke, Anita (Frontiers in Microbiology, 2015)
Serratia marcescens and several other bacteria produce the red-colored pigment prodigiosin which possesses bioactivities as an antimicrobial, anticancer and immunosuppressive agent. Therefore, there is a great interest to produce this natural compound. Efforts aiming at its biotechnological production have so far largely focused on the original producer and opportunistic human pathogen S. marcescens. Here, we demonstrate efficient prodigiosin production in the heterologous host Pseudomonas putida. Random chromosomal integration of the 21 kb prodigiosin biosynthesis gene cluster of S. marcescens in P. putida KT2440 was employed to construct constitutive prodigiosin production strains. Standard cultivation parameters were optimized such that titers of 94 mg/L culture were obtained upon growth of P. putida at 20 °C using rich medium under high aeration conditions. Subsequently, a novel, fast and effective protocol for prodigiosin extraction and purification was established enabling the straightforward isolation of prodigiosin from P. putida growth medium. In summary, we describe here a highly efficient method for the heterologous biosynthetic production of prodigiosin which may serve as a basis to produce large amounts of this bioactive natural compound and may provide a platform for further in-depth studies of prodiginine biosynthesis.